The effects of Mindfulness-Based Cognitive Therapy (MBCT) on cognitive skills in young soccer players - Seyed Mohammad Zadkhosh; Hassan Gharayagh Zandi; Majid Ghorbannejad (Exercise and Quality of Life)
TThe aim of this study was to examine the effect of Mindfulness-Based Cognitive Therapy training on mental skills of young soccer players. For this purpose, 30 soccer players were assigned to an experimental group of 15 players (intervention based on Mindfulness) and control group of 15 players that participations’ age ranged from 17 to 20 years old in provincial competitions in the year 2017-18. Athletes in the experimental group participated in MBCT course over eight weekly sessions of 2 h each. The control group did not receive any intervention. Before and after interventions Ottawa mental skills assessment tool questionnaire (Omsat-3) were used to collect data. The results of MANOVA showed that significant improvement in all sub-scales scores; Focusing (P=0.001), Refocusing (P=0.001), Imagery (P=0.001), Mental practice (P=0.001), and Competition planning (P=0.001) in the experimental group than control group. According to these findings, we concluded that Mindfulness-Based Cognitive Therapy training is appropriate to improve the level of cognitive skills of soccer players.